Kontekstualisasi Hadis 'Jangan Marah': Kritik atas Ujaran Kebencian di TikTok dalam Perspektif Double Movement - Healthy Habitue; Adynata (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to contextualize the prophetic tradition lā tagḍhab (“do not get angry”) as an ethical critique of hate speech on TikTok through Fazlur Rahman’s double movement hermeneutics. Using a qualitative library research design, data were collected through documentation techniques. Primary data consist of hadith narrations on the prohibition of anger found in Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, Sunan al-Tirmidhī, and Sunan Abī Dāwūd, as well as classical commentaries such as Fatḥ al-Bārī by Ibn Ḥajar al-ʿAsqalānī and Sharḥ Ṣaḥīḥ Muslim by al-Nawawī. Secondary data include scholarly works on double movement hermeneutics, studies on digital ethics and hate speech, official reports from the Indonesian Ministry of Communication and Digital Affairs, and online news reports concerning TikTok-related hate speech cases during 2025–2026. The analysis follows two stages: first, examining the historical context (asbāb al-wurūd) and classical interpretations of the hadith; second, extracting its universal moral values and applying them to contemporary digital communication practices. The findings reveal four universal ethical principles embedded in the hadith: self-control, moral strength, social harmony, and the prohibition of harming others through words or actions. These principles provide a critical framework for understanding hate speech on TikTok as a manifestation of uncontrolled digital anger amplified by algorithmic virality. The study demonstrates that double movement hermeneutics effectively bridges classical hadith teachings and contemporary digital challenges. Its novelty lies in positioning anger management as the foundational ethical principle for preventing hate speech, thereby contributing a hadith-based framework for digital literacy, online civic responsibility, and Islamic cyber ethics in the digital age